Agricultural Labour Productivity and Industrialisation: Lessons for Africa. (1st December 2017) - Diao, Xinshen; McMillan, Margaret; Wangwe, Samuel
Abstract: Using data from the Groningen Growth and Development Center's Africa Sector Database, we show that manufacturing employment and its share in total employment is growing in a number of African countries. We explore the extent to which this can be linked to agricultural productivity which has also been growing in much of Africa over the past two decades. We show that in countries that have successfully industrialised, there is a strong positive correlation between labour productivity growth in agriculture and the manufacturing employment share up until the point at which the manufacturing employment share peaks. Since 1996, there is also a positive correlation between labour productivity in agriculture and the manufacturing employment share in Africa. We explore the mechanisms behind these correlations and find evidence supporting the idea that increases in agricultural productivity have been associated with reductions in the employment share in agriculture and increases in income and the demand for locally produced products.